PELATIHAN PENGOLAHAN TOGA KEPADA KELOMPOK PKK DI KELURAHAN SUMUR DEWA KOTA BENGKULU - Suci Rahmawati; Delia Komala Sari; Riana Versita (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
One of the self-medication efforts that can be done by the community is the use of Family Medicinal Plants (TOGA). This Community Service activity was aimed to increase knowledge of the Family Welfare Program (PKK) group in Sumur Dewa, Bengkulu City about TOGA processing. The method was used in this activity is lecture and discussion. This service activity was carried out on September 21th, 2018. The results of questionnaire were showed that 50 of participants were 100% had known and planted TOGA in their home gardens, 72% had known the benefits of TOGA, 56% had known how to use TOGA. TOGA processing and 44% do not know how to process TOGA due to limited knowledge. From the implementation of this activity, it can be found that increases in the knowledge of the Sumur Dewa Village PKK group about TOGA after the activity.